MPA (Encyclopedia of Personality and Individual Differences, 2020)
OBJECTIVES: While the health risks associated with intrapancreatic fat deposition (IPFD) have attracted considerable attention, its contributing or risk factors remain poorly understood. Elevated uric acid (UA) levels are associated with multiple metabolic diseases. This study aimed to reveal the association between UA and IPFD. METHODS: A total of 9200 subjects who underwent computed tomography (CT) examinations for lung cancer screening were included. Data, including basic information (age, sex, BMI), laboratory tests, and medical history, were collected from the healthcare system. IPFD was defined based on three markers: pancreatic fat CT attenuation (PanCT) <40 HU, pancreas-to-spleen CT attenuation ratio (P/S) <0.8, and pancreatic CT attenuation value minus spleen CT attenuation value (P-S) <-5 HU. Logistic regression analysis and stratified analysis were employed to explore the association between uric acid and IPFD. RESULTS: Across all three pancreatic fat indicators, continuous UA was positively correlated with an elevated risk of IPFD (PanCT, odds ratio = 1.001, 95%confidence interval:1.000-1.002; P/S, OR=1.002, 95%CI:1.001-1.003; P-S, OR=1.002, 95%CI:1.001-1.003). A clear dose-response relationship was observed when UA was analyzed in quartiles. Participants in the highest UA quartile (Q4) had significantly elevated risks (PanCT, OR=1.534, 95%CI:1.220-1.930; P/S, OR=1.756, 95%CI:1.385-2.227; P-S, OR=1.747, 95%CI:1.482-2.059). Subgroup analysis revealed that this positive association was more pronounced in females. CONCLUSION: UA levels are positively associated with IPFD and is a valuable marker for IPFD management.